2007
DOI: 10.1124/jpet.107.124578
|View full text |Cite
|
Sign up to set email alerts
|

3-[5-(3,4-Dichloro-phenyl)-1-(4-methoxy-phenyl)-1H-pyrazol-3-yl]-2-m-tolyl-propionate (JNJ-17156516), a Novel, Potent, and Selective Cholecystokinin 1 Receptor Antagonist: In Vitro and in Vivo Pharmacological Comparison with Dexloxiglumide

Abstract: 3-[5-(3,4-Dichloro-phenyl)-1-(4-methoxy-phenyl)-1H-pyrazol-3-yl]-2-m-tolyl-propionate (JNJ-17156516) is a novel, potent, and selective cholecystokinin (CCK)1-receptor antagonist. In this study, the pharmacology of JNJ-17156516 was investigated both in vitro and in vivo, and the pharmacokinetic profile was evaluated in rats. JNJ-17156516 expressed high-affinity at the cloned human (pK I ϭ 7.96 Ϯ 0.11), rat (pK I ϭ 8.02 Ϯ 0.11), and canine (pK I ϭ 7.98 Ϯ 0.04) CCK1 receptors, and it was also highly selective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The observation that caerulein, an ancestral form of CCK with agonist activity at both CCK1 and CCK2 receptors, elevates plasma amylase activity and causes histological damage to the pancreas was the first observation linking CCK and pancreatitis (reviewed by Beglinger, 1999 ). Further studies showed that other CCK receptor agonists, such as CCK8S (the sulphated terminal eight amino acids of CCK; Morton et al , 2007 ), had similar effects and these effects could be blocked by selective, albeit low‐affinity, CCK1 receptor antagonists such as proglumide ( Niederau et al , 1985 , 1986 ). CCK concentrations are elevated in rat models of pancreatitis such as that induced by bile duct occlusion ( Toriumi et al , 1993 ) and intra‐bile duct injection of taurocholic acid ( Ohlsson et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that caerulein, an ancestral form of CCK with agonist activity at both CCK1 and CCK2 receptors, elevates plasma amylase activity and causes histological damage to the pancreas was the first observation linking CCK and pancreatitis (reviewed by Beglinger, 1999 ). Further studies showed that other CCK receptor agonists, such as CCK8S (the sulphated terminal eight amino acids of CCK; Morton et al , 2007 ), had similar effects and these effects could be blocked by selective, albeit low‐affinity, CCK1 receptor antagonists such as proglumide ( Niederau et al , 1985 , 1986 ). CCK concentrations are elevated in rat models of pancreatitis such as that induced by bile duct occlusion ( Toriumi et al , 1993 ) and intra‐bile duct injection of taurocholic acid ( Ohlsson et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…These observations led to the exploration of loxiglumide in clinical trials for the treatment of pancreatitis ( Ochi et al , 1999 ; Shiratori et al , 2002 ). The results of these studies were mixed, potentially because loxiglumide has complex pharmacokinetics ( Persiani et al , 2002 ) and relatively low affinity for the human CCK1 receptor ( Morton et al , 2007 ). Furthermore, these studies included patients who presented with pancreatitis already in its mid‐ to advanced stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of GI motility disorders, many novel therapies targeting different receptors are currently under investigation in both human and animal studies. These receptors include type‐2 chloride channel activators, CCK receptor antagonists, guanylate cyclase 2C agonists, and ileal bile acid transporter antagonists . Lubiprostone, a type‐2 chloride channel (CIC‐2) activator, activates chloride receptors located on gut epithelial cells and drives chloride ions into the gut lumen, inducing intestinal fluid secretion and increasing intestinal motility .…”
Section: Specific Pharmacological Interventionsmentioning
confidence: 99%
“…Lubiprostone, a type‐2 chloride channel (CIC‐2) activator, activates chloride receptors located on gut epithelial cells and drives chloride ions into the gut lumen, inducing intestinal fluid secretion and increasing intestinal motility . CCK‐1 (CCK‐1) receptor antagonists, including loxiglumide and dexloxiglumide, have been shown in animal and human studies to have an effect on the colonic muscle and improve colonic transit time . Guanylate cyclase 2C agonists, including linaclotide, bind to guanylate cyclase C receptors in the gut epithelium resulting in a large increase in secretion of chloride, bicarbonate anions, and fluid secretion into the gut thereby enhancing motility .…”
Section: Specific Pharmacological Interventionsmentioning
confidence: 99%